Somatización y Percepción Subjetiva de la Enfermedad - Di Silvestre, Cristina (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 1998)
In the present paper, a sociocultural perspective will be introduced to help explain the somatization phenomenon. Somatization is seem as one of the most frequent and problematic issues that faces physicians in primary health care. Somatization implies a discrepancy between the definition of the problem from the observer's point of view (e.g, the doctor) and the patient who experiences the pain (or other symptom) and discomfort in the body. The concept of illness behaviour as a subjective experience (meaning, cognition and coping), will be discussed; this concept illuminates the patient's point of view about his/her problem.